Ethnomathematical studies on the Gedong Songo temple - Amrizal Marwan Ali; Yasin Prasetia (Universitas Sarjanawiyata Tamansiswa, 2023)
The lack of information about designing buildings, measuring, patterning and calculating from ancient people, makes the concept of mathematics applied by people in the past remains unknown. It is necessary to study mathematics from a cultural point of view of society. This study is carried out through a cultural approach, or what is commonly referred to as ethnomathematics. Mathematics that is used by recognized cultural groups, such as national communities, ethnic groups, labor organizations, children of particular age groups, and professional classes, is known as ethnomathematics. Finding the mathematical principles used to construct the Gedong Songo Temple in Candi Village, Bandungan, Semarang Regency, Central Java, is the goal of this study. The object of research in this case is the Gedong Songo Temple. The approach taken is a qualitative one. In this study, an ethnographic technique was used. Data collection is done by literature study and observation. This research is structured descriptively, starting from reviewing problems related to ethnomathematics, formulating problems, collecting theories, analyzing, discussing data, and making conclusions. The findings demonstrated that geometry, symmetry, periodic patterns, and ratios are among the mathematical concepts used in the construction of the Gedong Songo Temple. The findings of this study can be used to improve mathematics instruction in cultural contexts. In addition, further studies on ethnomathematics can be carried out to see more comprehensively the mathematical concepts applied to the structure of the temple building.